Studi Kasus : Enteritis pada Kambing di Kabupaten Blitar - Wardhani, Hana Cipka Pramuda; Hermawan, Intan Permatasari; Kami, Krisantus PB (VITEK : Bidang Kedokteran Hewan, 2021)
A male goat aged 1 year was reported to have had 1 day of stool mixed with blood, decreased appetite and drinking, hair loss, thin body condition, soft stool consistency, lice, and liver worms. On further examination, temperature checks and other physical examinations were carried out, where the temperature of the goat was 39.0 and for physical examination of the goat there were lice, dull buu, and experienced weight loss so that it looked thin. Infusion of RL and Dextrose 5% SC, Bio ATP and B Complex 10 ml IM, Penstrep 7 ml IM, and Verm-O 1 tab Oral.